2023
DOI: 10.1186/s12870-023-04053-w
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted roles of Arbuscular Mycorrhizal Fungi in peanut responses to salt, drought, and cold stress

Abstract: Background Arbuscular Mycorrhizal Fungi (AMF) are beneficial microorganisms in soil-plant interactions; however, the underlying mechanisms regarding their roles in legumes environmental stress remain elusive. Present trials were undertaken to study the effect of AMF on the ameliorating of salt, drought, and cold stress in peanut (Arachis hypogaea L.) plants. A new product of AMF combined with Rhizophagus irregularis SA, Rhizophagus clarus BEG142, Glomus lamellosum ON393, and Funneliformis mosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 110 publications
1
10
0
Order By: Relevance
“…The stacked grana thylakoids in chili plants inoculated with AMF and sprayed with (ZnO-NPs + Se-NPs) were accompanied by the accumulation of starch granules, which indicates an increase in photosynthesis activity, as starch is the energy storage of the cells and is a product of photosynthesis. This agrees with the results obtained in [ 52 ] for peanuts and [ 56 ] for Cucumis melo L. In contrast, the number and size of plastoglobules within chloroplasts increased in the control plants. This agrees with the findings of [ 57 ], who observed that plastoglobules increased under cold stress because of their role in the active channeling of lipid molecules and lipid breakdown products.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The stacked grana thylakoids in chili plants inoculated with AMF and sprayed with (ZnO-NPs + Se-NPs) were accompanied by the accumulation of starch granules, which indicates an increase in photosynthesis activity, as starch is the energy storage of the cells and is a product of photosynthesis. This agrees with the results obtained in [ 52 ] for peanuts and [ 56 ] for Cucumis melo L. In contrast, the number and size of plastoglobules within chloroplasts increased in the control plants. This agrees with the findings of [ 57 ], who observed that plastoglobules increased under cold stress because of their role in the active channeling of lipid molecules and lipid breakdown products.…”
Section: Discussionsupporting
confidence: 92%
“…The combination of AMF inoculation and ZnO-NPs + Se-NPs as a foliar spray achieved an enhancement in most anatomical characteristics. The optimistic effect of AMF on the anatomical properties may be due to the vital role of AMF in mitigating crop abiotic stress by adjusting good root morphology using the extra-radical mycelium and improving the absorption of nutrients and water in the soil [ 52 ]. These findings are consistent with those reported by the authors of [ 53 ], who found that Zn and Se are crucial for promoting the chlorophyll scale and relieving all harmful outcomes caused by abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, a number of research groups including ours, have revealed the essential roles of AMF and Lactobacillus in crop resistance subjected to salinity stress (Diagne et al, 2020;Liu et al, 2023;Qin et al, 2021) Compared to sole application of AMF or LP, CMA showed a dramatic induction of plant height and biomass under both normalgrowth and salinity conditions, indicating the duplicate effect of CMA on peanut growth (Figure 1). Particularly, F v /F m in CMAtreated plant leaves were remarkably higher than those in AMF, LP and untreated leaves under soil salinity (Figure 1c,d), leading to an increased salinity tolerance in photosystem.…”
Section: Discussionmentioning
confidence: 96%
“…In the past decade, a number of research groups including ours, have revealed the essential roles of AMF and Lactobacillus in crop resistance subjected to salinity stress (Diagne et al, 2020; Liu et al, 2023; Qin et al, 2021); however, knowledge of the involvement of bacterial–fungal interactions in crop salinity tolerance requires further elucidation. Here we investigate, for the first time, the prominent roles of CMA (AMF and Lactobacillus ) in the alleviation of salinity‐induced damages in peanut plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation